Green and Anti-Green Grabbing: De-patrimonialization Policies in two Patagonian National Parks in Argentina - Ponzi, Brenda (2025)
Introduction: A process of national patrimonialization involves a public policy that transforms an area into a protected zone. When these areas obstruct capital accumulation, processes of de-patrimonialization are generated that allow legal and environmental difficulties to be avoided so that other agents, normally tourist agents, can develop their own projects. These processes can be understood within the frameworks of green and anti-green grabbing. Objective: this article analyses two cases in Argentina that present analogous processes of deregulation and re-commercialization of territory: the Cerro Catedral ski resort in Nahuel Huapi National Park and the península de Magallanes loaned area in Los Glaciares National Park. Methodology: A critical theoretical framework and a qualitative methodology based on a literature review and archival work was applied. Conclusions: In both cases, the initially protected areas were de-patrimonialized through various forms of transfer of responsibilities and territorial management. Among the main conclusions, it is clear that nature conservation did not help to halt the advance of commercialization; on the contrary, it formed part of processes that in the long term benefit the increase in profits of the concessionary companies, that is to say, that guarantee the accumulation, commercialization, and privatization.